Trauma to the nail complex - Jefferson Braga Silva; Samanta Gerhardt (Revista Brasileira de Ortopedia, 2014)
OBJECTIVE: to analyze the results from surgical intervention to treat trauma of the nail complex.METHODS: we retrospectively reviewed a series of 94 consecutive patients with trauma of the nail complex who were treated between 2000 and 2009. In 42 patients, nail bed suturing was performed. In 27 patients, nail bed suturing was performed subsequent to osteosynthesis of the distal phalanx. In 15, immediate grafting was performed, and in 10, late-stage grafting of the nail bed. The growth, size and shape of the nail were evaluated in comparison with the contralateral finger. The results were obtained by summing scores and classifying them as good, fair or poor.RESULTS: the results were considered to be good particularly in the patients who underwent nail bed suturing or nail bed suturing with osteosynthesis of the distal phalanx. Patients who underwent immediate or late-stage nail grafting had poor results.CONCLUSION: trauma of the nail complex without loss of substance presented better results than did deferred treatment for reconstruction of the nail complex.